The Consolation of Soldiers. Religious life in the Swedish army during the Great Northern War - Gudmundsson, David ; 0009-0003-0242-2426 (Scandinavian Journal of History, 2014)
It is commonly acknowledged that an elaborated military pastoral care provided a significant contribution to the efficiency of the Swedish army during the Great Northern War (1700–1721). Usually battle preparations and the chaplains’ efforts to instil morale and discipline among the soldiers are emphasized. In this article my aim is to provide a somewhat different idea on the nature of the religious life in the army of Charles XII. By focusing in turn on the chaplains’ duties, the military sermons, the hymns sung in the army and the soldiers’ reading of prayer books, I point at the similarities between military and civilian religious life in early 18th-century Sweden.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Centre for Theology and Religious Studies (015017000)
Keywords: Great Northern War; military pastoral care; chaplains; sermons; hymns; prayer books